(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of this study was to determine dental laser education and knowledge among dental graduates in Tamil Nadu.Methodology: This cross-sectional questionnaire based study included general dental practitioners and specialists from various fields, academicians and students. The study was during the period of January to March 2020.The self-administered questionnaire consisted of questions pertaining to laser education and knowledge of dental laser applications sent randomly to 100 participants. Results: In the light of the study presented above we can conclude that majority of the PG participants were aware of the concept of laser education than UG that indicated that awareness has to be created among such UG students through survey and other modes of information it also shows that majority of 79% males were more aware than the rest of females. It was also observed among the age groups 23-25 the participants had the highest awareness and a majority of 32.67% of these participants had an interest in dental laser education this shows that the number of participants that are interested is not satisfactory hence, such surveys must be carried out more often to until advanced awareness regarding dental laser education as it is the future of dentistry in the upcoming era.Conclusion: This study strongly concluded there must be Dental curriculum teaching at least 3-4 hrs about the application and implementation. In this technological era, an exponential usage in lasers should be made possible by reducing its production costs with high standards. It shows that the majority of 79% males were more aware than the rest of females. It was also observed among the age groups 23-25 the participants had the highest awareness and a majority of 32.67% of these participants had an interest in dental laser education.